Development of The Momon Adventure HTML5 Canvas Game Based on Website - Panjaitan, Cherlina Helena Purnamasari (Gameology and Multimedia Expert, 2024)
The development of games is increasingly rapid, followed by tools for making games. There are many game genres, Platform Games or Platformers is one of them. Platform games are a genre of video games whose main objective is to control a character who jumps or climbs between platforms to achieve a specific goal. Platformers are characterized by level designs that feature terrain that varies in challenge and demands the player character's abilities (such as jumping and climbing) to navigate the player's environment and achieve the objectives in each level. For example, there are many famous platformer games such as Super Mario, Sonic, Metal Slug and so on. This game is inspired by the game Fly Bird. This development uses HTML 5 Canvas and uses the Javascript programming language.